2018
DOI: 10.1016/j.commatsci.2018.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Electric field effect in boron and nitrogen doped graphene bilayers

Abstract: Unlike single layer graphene, in the case of AB-stacked bilayer graphene (BLG) one can induce a non-zero energy gap by breaking the inversion symmetry between the two layers using a perpendicular electric field. This is an essential requirement in field-effect applications, particularly since the induced gap in BLG systems can be further tuned by the magnitude of the external electric field. Doping is another way to modify the electronic properties of graphene based systems. We investigate here BLG systems dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…Basically, the opening of a bandgap in graphene is achieved by a symmetry breaking of the hexagonal structure of graphene [17]. Therefore, several methods have been proposed to break the high symmetry of monolayer and bilayer graphene, such as strain [18,19], magnetic field [20], oxidation [21], application of a transverse electric field [22,23], chemical modification [24,25], and doping processes [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the opening of a bandgap in graphene is achieved by a symmetry breaking of the hexagonal structure of graphene [17]. Therefore, several methods have been proposed to break the high symmetry of monolayer and bilayer graphene, such as strain [18,19], magnetic field [20], oxidation [21], application of a transverse electric field [22,23], chemical modification [24,25], and doping processes [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…3, for zero electric field and an electric field | E field | = 5 V/nm perpendicular to the graphene sheets, with the two possible orientations. The position of the energy gap is systematically modified by the external electric field, as already indicated for B and N doped BLGs [21]. The gaps introduced by either B or N substitutions were also found in the context of disorder using the random tight-binding model [40].…”
Section: B Electronic Propertiesmentioning
confidence: 61%
“…In this paper we are particularly focused on the combined effect of doping and external electric field. We already showed that the effective doping by boron or nitrogen can be systematically modified by an applied electric field [21]. It was also established that dual doping by B and N, opens a gap at zero field in a BLG system.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The electronic properties of a BLG have been studied using density functional theory (DFT), in which the bandgap at the K point in the Brillouin zone depends linearly on the average applied electric field [9,10]. One of the main approaches to alter the electrostatic potential of a BLG is substitutional doping with foreign atoms [11] such as Boron (B), Nitrogen (N) [12], and Silicon (Si) atoms. For instant, a B-and N-doped BLG results in a p-type or an ntype semiconducting behavior with a shifting of the Fermi energy, respectively.…”
Section: Introductionmentioning
confidence: 99%